Accuracy of non-gated low-dose non-contrast chest CT with tin filtration for coronary artery calcium scoring. (2022) - Liu, Ying; Chen, Xuezhi; Liu, Xianchen; Yu, Hao; Zhou, Lianjun; Gao, Xiaoling; Li, Qinglin; Su, Shujun; Wang, Lin; Zhai, Jia
Abstract: Objective: The study investigated the accuracy of coronary artery calcium scores (CACS) and the potential for reducing radiation dose using non-gated low-dose non-contrast chest computed tomography (CT) scanning with tin filtration for one-stop screening of the lungs and heart. Methods: A prospective study was conducted, 193 Patients received two scans for determining CACS, including an ECG-gated CT at 120 kV (ECG-gated CT), followed by a non-gated low-dose chest CT using 100 kV with tin filtration (non-gated Sn100 kV-LDCT). The Agatston score (AS), risk stratification, and radiation dose were compared between the scan types. Results: There was good consistency in the AS from both an ECG-gated CT and a non-gated low-dose chest CT scan, which had a high correlation (r = 0.970). The Kappa value of risk stratification of the two scan types was 0.549. The area under the ROC curve (AUC) of the CACS was used to develop a new risk stratification standard for non-gated Sn100 kV-LDCT evaluation of CACS. In comparison to the CACS measured by ECG-gated CT, non-gated Sn100 kV-LDCT had an AUC of 0.951 and an optimal critical value of 4.6 in the low-risk category. The AUC of low-medium risk was 0.966, and the optimal critical value was 41.2. The AUC of the medium-high risk category was 0.968, and the optimal critical value was 230. The consistency in CACS measured by ECG-gated CT and non-gated Sn100 kV-LDCT had a Kappa value of 0.831. The Effective dose (ED) of non-gated Sn100 kV-LDCT and ECG-gated CT was 0.056 ± 0.017 mSv and 0.685 ± 0.455 mSv, respectively (p < 0.05). Conclusion: The Agatston score of CACS using non-gated low-dose chest CT was accurate, but there was an underestimation in risk stratification. This study developed a new risk stratification standard for non-gated Sn100 kV-LDCT evaluation of CACS, which is in closer agreement with CACS derived from ECG-gated CT scans.